2019
DOI: 10.3390/ijerph16224317
|View full text |Cite
|
Sign up to set email alerts
|

Quick Analysis of Organic Amendments via Portable X-ray Fluorescence Spectrometry

Abstract: The determination of heavy metals in soils and organic amendments, such as compost, manure, biofertilizer, and sludge, generally involves the digestion of samples with aqua regia, and the determination of those in the solution using various techniques. Portable X-ray fluorescence (PXRF) has many advantages in relation to traditional analytical techniques. However, PXRF determines the total elemental content and, until now, its use for the analysis of organic amendments has been limited. The objective of this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
(35 reference statements)
0
13
1
Order By: Relevance
“…Either way, the results show that randomized cross validation and hold-out validations are essential to interpret model accuracy and reliability. Our results indicate that MIR + machine learning is not yet a proven method to infer Mg and Mn concentrations in OA, contradicting the study of López-Núñez et al [ 36 ] who claimed good calibrations for pXRF and a wide range of nutrients and contaminants in very similar OA (but the study did not include validations). MIR did not produce useable models for trace elements (Ni, Cu, Zn) or contaminants (Cd, Pb), while both machine learning model types produced useable models from XRF data; this is an unsurprising conclusion as these elements all have fluorescence peaks identifiable to low levels with XRF.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Either way, the results show that randomized cross validation and hold-out validations are essential to interpret model accuracy and reliability. Our results indicate that MIR + machine learning is not yet a proven method to infer Mg and Mn concentrations in OA, contradicting the study of López-Núñez et al [ 36 ] who claimed good calibrations for pXRF and a wide range of nutrients and contaminants in very similar OA (but the study did not include validations). MIR did not produce useable models for trace elements (Ni, Cu, Zn) or contaminants (Cd, Pb), while both machine learning model types produced useable models from XRF data; this is an unsurprising conclusion as these elements all have fluorescence peaks identifiable to low levels with XRF.…”
Section: Discussioncontrasting
confidence: 99%
“…López-Núñez et al [36] who claimed good calibrations for pXRF and a wide range of nutrients and contaminants in very similar OA (but the study did not include validations). MIR did not produce useable models for trace elements (Ni, Cu, Zn) or contaminants (Cd, Pb), while both machine learning model types produced useable models from XRF data; this is an unsurprising conclusion as these elements all have fluorescence peaks identifiable to low levels with XRF.…”
Section: Plos Onementioning
confidence: 97%
“…The results showed that Zn predictions were of high accuracy and good model agreement (Table 6). López-Núnez et al [25] showed a similar high accuracy of predicted Zn in organic amendments with a linear model. Hence, predictions of Zn concentrations with PXRF appear highly suitable.…”
Section: Sewage Sludge Applicationmentioning
confidence: 72%
“…The Fe(m) readings further improved Equation (17). The P(m) readings showed a correlation with Se(ae) and Equations (19) and (20) used P(m). The second coefficients in these equations were Fe(m) and Ba(s).…”
Section: Linear Relationships In Sewage Sludge Samplesmentioning
confidence: 94%
“…The soil mode is based on Compton normalization and is often used for scanning and detection for soil metallic elements [4] at low concentrations (<1%). In this mode, readings were obtained for the following elements: Mo (19), Zr (29), Sr (30), Rb (30), Pb (24), As (15), Zn (30), Cu (28), Ni (12), Fe (30), Mn (26), Cr (17), V (14), Ti (29), Sc (28), Ca (30), K (30), S (30), and Ba (18). Furthermore, U (5), Th (5), Au (0), Se (0), Co (0), Hg (0), W(0), Cs (5), Te (0), Sb (1), Sn (6), Cd (0), Ag (4), and Pd (0) were included in soil mode, although they were below the LODs in almost all samples and they were not used in the following.…”
Section: Field Portable X-ray Fluorescence (Pxrf) Analysismentioning
confidence: 99%